The ‘black fungus' Co-Infection in COVID-19 Patients : A Review - Hadiyanto, Jessica Novia; Wilda, Friska; Cahyadi, Alius; Adisuhanto, Marcella (Institute of Topical Disease Universitas Airlangga, 2021)
Mucormycosis is one type of fungal disease, associated with a poor prognosis if not promptly diagnosed and managed because its highly aggressive tendency. Although it is a rare disease, a rapid increase in cases of mucormycosis associated with COVID-19 is being reported. Mostly, risk factors for this disease are uncontrolled diabetes mellitus, other immunosuppressive conditions and corticosteroid therapy. Immune dysfunction, lung pathology and corticosteroid therapy in COVID-19 patients making it more susceptible to develop fungal infection including mucormycosis. The combination of steroid therapy and underlying diabetes mellitus in COVID-19 also can augment immunosuppression and hyperglycemia. Control of hyperglycemia, early treatment with liposomal amphotericin B, and surgery are three important factors in mucormycosis therapy that essential for successful management. However, in this COVID-19 pandemic situation, that management strategies are compromised. First, hyperglicemia can be aggravated by glucocorticoid, therapy that used widely for COVID-19 especially in severe case. Second, patients with ARDS and multiorgan dysfunction can prevent timely diagnostic for imaging and other testing, so appropriate therapy that should be given will be delayed. Last, the essential service in hospital such surgery in this pandemic era reduced signiï¬ cantly to prevent the spread of COVID-19. This review was created with the aim mucormycosis co-infection can be considered in patients with COVID-19, especially with known risk factor. Prompt and rapid diagnosis are important for eï¬€ ective therapy and decreasing case fatality rate. The use of steroid in mild cases, utilization of higher doses of steroid and drugs that targeting immune pathway should be avoided.